KONTRIBUSI FAKTOR PENDIDIKAN TERHADAP USIA PERKAWINAN PERTAMA WANITA DI KECAMATAN TRANGKIL KABUPATEN PATI - Lusiana Febryanti (Universitas Negeri Semarang, 2015)
The study aims determine: (1) the average age at first marriage of women in the study site, (2) Factorsaffecting the age at first marriage of women. (3) Contribution to educational factors age at first marriage ofwomen. Sampling was done by using area sampling technique taken from 3 villages namely Trangkil (urbanareas),Kajar Village(sub urban area) and the Village Tegalharjo (rural area).The Data collectiontechniques are the documentation, and questionnaires. The data analysis techniques used are descriptivepercentages and regresi. The average age at first marriage of women in urban areas is 20,41 years , suburbanareas is 19,97 years, rural area is 18, 7 years based on regression analysis factors of education,parental socio-economic conditions, perceptions of marriage age to accuse influential age at first marriage.Contribution of education in urban areas is 35,5%, sub-urban areas is 26,5%, and rural areas is 39.4%. Itcan be concluded that the average age of marriage in urban, sub-urban, and rural is varied. Factorsaffecting age at first marriage of woman include educational factors, socio-economic conditions of theparents, the perception of the age of first marriage, the contribution of education to the highest marriage ageis in rural areas, and the smallest is in the sub-urban areas.